Development of an E-worksheet Based on Problem-Based Learning with Prompting Question Technique on Chemical Equilibrium Material - Amanda, Putry; Syolendra, Dwi Finna (Jurnal Pijar Mipa, 2025)
Students' misunderstandings and low level of active involvement in learning chemical equilibrium and the incomplete application of problem-based learning models. This study was motivated by students' misconceptions and low active involvement in learning chemical equilibrium material. In addition, the implementation of the problem-based learning model has not been fully realized, and students still experience difficulties in connecting and applying chemical concepts to everyday life. The purpose of this study is to develop a problem-based learning e-worksheet with prompting question techniques on chemical equilibrium material that is valid and practical. The method used is research and development (R&D) with the Plomp model, which includes the preliminary research and prototyping phases. Validity analysis techniques were analyzed using Aiken's V scale, and practicality analysis techniques were analyzed using a percentage formula. The validity analysis yielded an average score of 0.925, which is considered valid. The practicality test results showed that the e-worksheet is highly practical, with an average score of 94.375% from teachers and 89.38% from students. Based on the results of the study, it can be concluded that the development of an e-worksheet based on problem-based learning with prompting question techniques on chemical equilibrium material is valid and very practical.